PENGEMBANGAN KOMIK ETNOMATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD - Putri, Hellen Silvia Meilana; Sutriyani, Wulan (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
The purpose of this study was to design and test the effectiveness of a learning medium in the form of an Ethnomathematics Comic at SDN 2 Tanjung, Pakis Aji District, Jepara Regency, during the 2024/2025 academic year. The research focused on improving the mathematics learning outcomes of first-grade students, particularly in basic arithmetic operations—addition and subtraction—by integrating local wisdom. The research method employed in this study was Research and Development (R&D) using the ADDIE model, which consists of five main stages: Analysis, Design, Development, Implementation, and Evaluation. The results of the preliminary analysis indicated that students’ interest and achievement in mathematics were still relatively low. This condition highlights the need for the development of more innovative, engaging, and relevant learning media to enhance students’ motivation and learning outcomes. The developed comic incorporates elements of Indonesian local culture and includes interactive features, such as QR codes that link to digital materials. Validation by experts indicated that the media was feasible for use, with scores of 78% for graphic and presentation aspects and 85% for material aspects. The practicality test also showed positive results, with teacher evaluations reaching 93% and student evaluations 87%. Effectiveness analysis using a paired t-test revealed a significant difference between the pretest and posttest scores (Sig. 0.000), with an N-gain value of 1.00, indicating that the media was highly effective. In conclusion, the Ethnomathematics Comic proved to be a valid, practical, and effective learning medium for improving students’ mathematics learning outcomes. The study recommends further development of similar media for other topics and grade levels, as well as broader implementation and testing. ABSTRAKTujuan penelitian ini adalah merancang serta menguji efektivitas media pembelajaran berupa Komik Etnomatematika di SDN 2 Tanjung, Kecamatan Pakis Aji, Kabupaten Jepara, pada tahun ajaran 2024/2025. Fokus penelitian diarahkan pada peningkatan hasil belajar matematika siswa kelas I, khususnya dalam materi operasi hitung dasar, yaitu penjumlahan dan pengurangan, dengan mengintegrasikan kearifan lokal. . Metode penelitian yang digunakan dalam penelitian ini adalah Research and Development (R&D) dengan model ADDIE. Model tersebut terdiri atas lima tahapan utama, yaitu Analisis, Desain, Pengembangan, Implementasi, dan Evaluasi. Berdasarkan hasil analisis awal, diketahui bahwa minat dan prestasi belajar siswa pada mata pelajaran matematika masih tergolong rendah. Kondisi tersebut menunjukkan perlunya pengembangan media pembelajaran yang lebih inovatif, menarik, dan relevan untuk meningkatkan motivasi serta hasil belajar siswa. Komik yang telah dikembangkan mengandung unsur budaya lokal Indonesia dan dilengkapi dengan fitur interaktif, seperti QR code yang menghubungkan ke materi digital. Validasi dari para ahli menilai media ini layak digunakan, dengan skor 78% untuk aspek grafis dan penyajian, serta 85% untuk aspek materi. Uji kepraktisan menunjukkan hasil yang baik, dengan penilaian guru mencapai 93% dan peserta didik 87%. Analisis efektivitas menggunakan uji t berpasangan memperlihatkan perbedaan yang cukup signifikan antara nilai pretest serta nilai posttest (Sig. 0,000), dengan N-gain sebesar 1,00, yang mengindikasikan media ini sangat efektif. Kesimpulannya, Komik Etnomatematika terbukti sebagai media yang memenuhi kriteria validitas, kepraktisan, serta efektivitas untuk meningkatkan hasil belajar matematika peserta didik. Penelitian ini menyarankan pengembangan media serupa untuk materi dan jenjang kelas lainnya serta pengujian dalam cakupan yang semakin luas.